R.S. Belkin and the Development of Views on Quality Management in Forensic - S. A. Smirnova; S. A. Kuz’min (Теория и практика судебной экспертизы)
The article presents the authors' perspective on the issues of the genesis of scientific ideas concerning organizational aspects of forensic practice, and specifically systems for ensuring its quality and effectiveness. Key stages in the transformation of the concept of scientific organization of labor into the system of international quality standards and their influence on the organization of forensic practice are examined. Further highlighted are Professor R.S. Belkin's outstanding contributions to establishing the theoretical principles of quality management and their dialectical development in forensic expertology.